A STYLISTIC ANALYSIS OF NEWSPAPER HEADLINES ON THE REPORTED DEATH OF FORMER PRESIDENT MUHAMMADU BUHARI IN SELECTED NIGERIAN NEWSPAPERS - ALABI , Moshood Abimbola (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
As we use language in every interaction, it serves specific purposes in various environments among different individuals. This study investigates the features of the language of newspaper headlines on the recent death of the former president Muhammadu Buhari. The qualitative approach of data analysis has been adopted in this research. Six prominent Nigerian newspapers have been selected for the content analysis of their headlines. The headlines chosen from the selected newspapers are presented and analysed through the foregrounding theory of stylistics. It is obvious that each headline has a purpose and is meant to achieve some psychological effects on the readers. It is also an undeniable fact that it is meant to capture the gist of the story. The implication of this study is very significant, as it can be used to account for many unwritten underlying factors that determine how headlines are written. It contributes to our understanding of the styles of writing headlines, the motive behind the construction of a headline, and the effects of the headlines on the readers.